Association between perceived neighbourhood characteristics, physical activity and diet quality: results of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). (December 2016) - Chor, Dóra; Cardoso, Letícia; Nobre, Aline; Griep, Rosane; Fonseca, Maria; Giatti, Luana; Bensenor, Isabela; del Carmen Bisi Molina, Maria; Aquino, Estela; Diez-Roux, Ana; de Pina Castiglione, Débora; Santos, Simone
Abstract Background The study explores associations between perceived neighbourhood characteristics, physical activity and diet quality, which in Latin America and Brazil have been scarcely studied and with inconsistent results. Methods We conducted a cross-sectional analysis of 14, 749 individuals who participated in the Brazilian Longitudinal Study of Adult Health (Estudo Longitudinal de Saúde do Adulto, ELSA-Brasil) baseline. The study included current and retired civil servants, aged between 35 and 74 years, from universities and research institutes in six Brazilian states. The International Physical Activity Questionnaire (IPAQ) long form was used to characterize physical activity during leisure time and commuting; additional questions assessed how often fruit and vegetables were consumed, as a proxy for diet quality. Neighbourhood characteristics were evaluated by the "Walking Environment" and "Availability of Healthy Foods" scales originally used in theMulti-Ethnic Study of Atherosclerosis (MESA). Associations were examined using multinomial logistic regression. Results Perceiving a more walkable neighbourhood was positively associated with engaging in leisure time physical activity and doing so for longer weekly. Compared with those who saw their neighbourhood as less walkable, those who perceived it as more walkable had 1.69 (95 % CI 1.57–1.83) and 1.39 (1.28–1.52) greater odds of engaging in leisure time physical activity for more than 150 min/week or up to 150 min/week (vs. none), respectively. Perceiving a more walkable neighbourhood was also positively associated with transport-related physical activity. The same pattern was observed for diet: compared with participants who perceived healthy foods as less available in their neighbourhood, those who saw them as more available had odds 1.48 greater (1.31–1.66) of eating fruits, and 1.47 greater (1.30–1.66) of eating vegetables, more than once per day. Conclusions Perceived walkability and neighbourhood availability of healthy food were independently associated with the practice of physical activity and diet quality, respectively, underlining the importance of neighbourhood-level public policies to changing and maintaining health-related habits.